From malpractice to patient safety: A framework for analysing harmful events, system vulnerabilities, and adaptive surgical expertise in neurosurgery – A Swiss perspective - Gerhard Hildebrandt (Journal of Patient Safety and Risk Management, 2026)
Background The assessment of medical malpractice has traditionally focused on legal responsibility and individual accountability. However, legal classifications may provide only limited insight into mechanisms leading to patient harm and may therefore not fully support the development of preventive patient safety strategies. This challenge may be particularly relevant in neurosurgery, where unexpected intraoperative events frequently require adaptive decision-making beyond routine algorithms. Objective This perspective proposes a patient safety-oriented framework for the analysis of harmful neurosurgical events, using the Swiss healthcare system as an illustrative example. Conceptual framework The proposed approach consists of three complementary elements: (1) a taxonomy distinguishing errors, negligence, safety incidents, and adverse events; (2) a legally supported, independent reporting and analysis platform designed to facilitate transparent system learning and non-punitive evaluation of treatment-related harm; and (3) greater emphasis on the development of adaptive surgical expertise and organisational structures capable of managing non-routine intraoperative crises. Conclusions Complementing traditional legal assessments of malpractice with systematic analyses of mechanisms of harm, safety barriers, and adaptive surgical performance may provide a comprehensive approach to improving neurosurgical safety culture. A framework integrating transparent reporting, multidisciplinary learning, and preparation for unexpected intraoperative challenges may contribute to the prevention of future patient harm.